Cheap and Dirty: The Effect of Contracting Out Cleaning on Efficiency and Effectiveness. (25th February 2019) - Elkomy, Shimaa; Cookson, Graham; Jones, Simon
Abstract: Contracting out of public services, especially ancillary services, has been a key feature of New Public Management since the 1980s. By 2014, more than £100 billion of U.K. public services were being contracted out annually to the private sector. A number of high‐profile cases have prompted a debate about the value for money that these contracts provide. Value for money comprises both the cost and the quality of the services. This article empirically tests the contestability and quality shading hypotheses of contracting out in the context of cleaning services in the English National Health Service. Additionally, a new hypothesis of coupling is presented and tested: the effect of contracting of ancillary services on patient health outcomes, using the hospital‐acquired infection rate as our measure. Using data from 2010–11 to 2013–14 for 130 National Health Service trusts, the study finds that private providers are cheaper but dirtier than their in‐house counterparts .